A profile of emergency departments in Baghdad hospitals - Riyadh Khudhair Lafta; Saja Abdusattar Mohammed (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess the structure as well as availability of essential equipment and medicine at emergency departments. Method: The descriptive, cross-sectional study was conducted from March to June 2021 after approval from the ethics review committee pf the College of Medicine, Mustansiriyah University, Baghdad, Iraq, and comprised emergency departments of general and teaching hospitals in the city. Evaluations were done using the World Health Organisation checklist and the guidelines of the Australasian College for Emergency Medicine related to Emergency Department Design. Results: Of the 26 secondary care hospitals in Baghdad, 13(50%) were evaluated. Triage was not available in 8(62%) hospitals, resuscitation room in 10(77%) and waiting room in all the 13(100%). An obvious shortage of medicines and vaccines was noted in 11(85%) hospitals. Coronary care unit and intensive care unit were not close to the emergency department in 7(54%) hospitals, and liaison psychiatry and social work links were not available in all 13(100%) hospitals. Conclusion: There is a need to improve service delivery at emergency departments functioning at hospitals in Baghdad. Key Words: Coronary Care, Emergency, World Health Organization, Social Work, Psychiatry, Vaccines